A panel data analysis on the relationship between corporate governance and bank efficiency - Adnan, Muhammad Akhyar; Htay, Sheila Nu Nu; Ab. Rashid, Hafiz Majdi; Mydin Meera, Ahamed Kameel (World Business Institute, Australia, 2011)
Emerging corporate governance issues in the Asian countries due to the 1997-1998 economic crises makes it much more important to discuss those issues within the context of this region. In developing countries such as Malaysia, a good governance of the banks is crucial for the survival of its economy. Many studies have tried to link the effect of corporate governance on banks’ efficiency (Jain and Thomson, 2008; Chunxia, Shujie and Zongyi, 2009; Lensink, Meesters and Naaborg, 2008). This study investigates the impact of corporate governance on efficiency of Malaysian listed banks by using a panel data analysis. Corporate governance variables are represented by board leadership structure, board composition, board size, director ownership, institutional ownership and block ownership. Bank efficiency is used to measure the performance since traditional accounting and market performance measures are doubtful in suitability of capturing the actual performance of the banking industry and efficiency seems to be given more attention recently (e.g. Ihsan and Kabir, 2002). The findings show that smaller board size and higher percentage of block ownership lead to better efficiency of Malaysian banks. The current prevailing situations in Malaysia are discussed to highlight the reasons behind these research findings.